Isolasi dan Identifikasi Molekuler Bakteri Pelarut Fosfat dari Gua Gamelan di Kawasan karst Kiskendo Kendal, Jawa Tengah - Mahmudah, Hawari Rosdiana; Suprihadi, Agung; Budiharjo, Anto (Berkala Bioteknologi, 2022)
Phosphate solubilizing bacteria is a group of bacteria that dissolves unavailable phosphate into the form that can be absorbed by plants. This research aimed at isolation and moleculer identification of phosphate solubilizing bacteria based on 16s rRNA from bat cave guano and potential microorganisms which were able to dissolved phosphate. Several stages of this research are, isolation PSB in Pikovskayaand NBRIP agar, Gram staining, and molecularidentification. The isolation result obtained two isolates phosphate solubilizing bacteria, which are G4-1 and G5. Isolate G5 is the highest on solubilizing phosphate with a diameter of clear zone 22.01 mm, and Isolate G4-1 exhibited diameter of clear zone 19.8 mm. Isolates G4-1 and G5 are the gram-negative bacteria. DNA amplification of these bacteria employing universal primers 27 F (5’-AGAGTTTGATCMTGGCTCAG-3’) dan Primer 1492 R (5’-GGTTACCTTGTTACGACTT-3’) generated the 1520 bp and 1235 bp PCR product. The result of the analysis of 16s rRNA gene sequence showed that isolate G4-1 has 80% similarity with Acinetobacteriwofii strain-JCM partial sequence, and isolate G5 has 92% similarity with Serratia marcesens strain-NBRC.